Design of Industrial Practice and Thesis Monitoring Information System (SIPIKRI) In Informatics Engineering Study Program, State University of Surabaya - Ronggo Alit; Agus Prihanto; Aditya Prapanca (IJCONSIST JOURNALS, 2023)
Abstract— Industrial Practice Activities are a place for students to gain experience in the world of work and research experience in the form of a thesis by practicing the theories they have learned in lectures. In addition, it is also a place where students express their ideas, scientific ideas and produce research results and products before they become a Bachelor. The mechanism for appointing supervisors and examiners as well as scheduling Industrial Practice and thesis in the Informatics Engineering study program is carried out by the study program through the administration while the schedule and examination team are informed via messages to each examiner. Previously, there was a system that only solved the problem of industrial practice activities, namely the Web-based Industrial Practice Monitoring Information System, which is a system that can provide information about industrial practice programs online. This system has advantages in terms of the speed of presenting the information produced. In addition, this system is web-based so that it can be accessed at any time. This process takes a long time and good management, so that students get supervisors who are in accordance with their fields of expertise and the right exam schedule so that it does not interfere with the lecture schedule and lecturer schedule, but the same problem arises related to student thesis activities. then a system is needed that can solve problems that arise related to thesis activities. The conclusion that can be drawn in this study is the production of the Industrial Practice and Thesis Monitoring Information System (SIPIKRI) which can help the Informatics Engineering study program, Faculty of Engineering, Surabaya State University to run smoothly. In addition, it is hoped that this information system can assist the work of informatics engineering study program managers in carrying out the administration of these activities. Keywords— Information systems, Industrial Practice and Thesis, Monitoring